Konsep Akhlak Guru, Peserta Didik Perspektif Az-Zarnuji Dalam Kitab Ta’limul Muta’allim - Irwan Irwan; Marfuda (Jurnal Ilmiah Tarbiyah Umat, 2025)
Abstract Humans are basically the most noble and most perfect creatures, especially if humans are adorned with knowledge and character. The presence of this article specifically discusses the concept of teacher morals, students from the perspective of Az-Zarnuji in the book of ta'limul muta'allim, using the literature research method is a type of research that consistently collects various sources of literature from various books. The results of the study of the teacher's obligation to always maintain not to humiliate himself with greed, greed for worldly life, humble himself, and protect himself from haram matters. Students give knowledge generously, pray humbly, ask lots of questions, think with their hearts, give lots of charity, do lots of dhikr and give kindness to teachers, thank Allah SWT a lot, believe that knowledge, help, guidance, come from Allah SWT. So the concept of morals for teachers and students in the book ta'limul muta'allim is very relevant as a guide in facing our generation in this modern era which is in a critical situation, especially in our beloved country, the Republic of Indonesia.